NARCISSISTIC CULTURE – SOCIAL ANOMALY OR NORM? - Јована Д. Вурдеља (Filolog, 2021)
Based on the book of Christopher Lasch, The culture of narcissism (American life in the age of diminishing expectations), by exploring narcissism as a clinical as well as growing civilisational and social phenomenon in the context of metaphor of the human condition, this paper problematises a cultural crisis of the American society in the second half of the 20th century, eroded by corrosive decadence and atrophied intellectual and moral standards along with cultural values diagnosed as narcissistic. Crucial symptoms of the observed pathological changes in the cultural and social climate are also articulated with special reference to the transition from the erosion of standards to the apotheosis of individualism and solipsism. At the same time, the expansion of narcissistic ideology in the 21st century is considered in the form of reﬂection in today's selfie culture, as well as the fact that narcissistic personality disorder should no longer be considered a psychological deviation, but rather a dominant social norm, which implies a new narcissistic conformism.